The Book of Isaiah: Patchwork of literary fragments versus predetermined literary structure? Part I - Kruger, HAJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
The rhetoric of the book of Isaiah is partially based on different forms of parallelism. The elementary form of this technique is well-known, namely the development of an idea by repeating it. Until recently studies dealing with this literary phenomenon were mostly restricted to the identification of parallelisms within phrases, sentences and short passages in the Old Testament. Presently however, examples of more extensive parallelisms, including comprehensive chiastic (crosswise) and other patterns, are under investigation in the book. Apart from the identification of encompassing bifid structures, new possibilities include the identification of so-called triadic2 and quadratic patterns which may span several passages. Reading the book as literature with a view to identifying overarching structures, it will hopefully become clear in this review that the techniques concerned and as operative in the book of Isaiah have been expanded beyond their basic forms, giving new impetus to this approach.